Calibration of densitometry in radio-isotopic in situ hybridization - Ruijter, Jan M. (Image analysis and stereology, 2001)
Densitometry on autoradiographs of sections processed for in situ hybridization provides a direct measure for the in situ quantification of mRNA. Gelatin spots, containing different concentrations of the radioisotope, and processed measurements. The shape of the gelatin spots was shown to be circular with a parabolic cross-sectional profile. This sample shape allows the subdivision of the spot into series of concentric rings, which enables an unbiased measurement of the optical density - radioactivity relation. This spot measurement is also applicable to DNA arrays spotted on glass or membranes. A new model, explaining the optical density of autoradiographs, wasderived and fitted to the calibration points. The use of this calibration method is crucial for the correct interpretation of autoradiographs.
Keywords: Avtoradiografija; Calibration; Densitometry; Denzitometrija; Hibridizacija in situ; In situ hybridization; Kalibracija; Autoradiography; Želatina; Rna, messenger; RNA, prenašalna; Gelatin; molecular biology; molekularna biologija